2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8968598
|View full text |Cite
|
Sign up to set email alerts
|

A VR System for Immersive Teleoperation and Live Exploration with a Mobile Robot

Abstract: Applications like disaster management and industrial inspection often require experts to enter contaminated places. To circumvent the need for physical presence, it is desirable to generate a fully immersive individual live teleoperation experience. However, standard video-based approaches suffer from a limited degree of immersion and situation awareness due to the restriction to the camera view, which impacts the navigation. In this paper, we present a novel VR-based practical system for immersive robot teleo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…We find very appropriate the suggested use of a small number of tasks, and we wish these to follow the order given by the MANTRA as it fits nicely to robot teleguide actions. We always Overview first, while Zooming, Filtering and Details are applied on demand [31] [35]. Automatic adaptation based on speed and distance to objects is an available option useful for specific environments and situations.…”
Section: Adaptive Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…We find very appropriate the suggested use of a small number of tasks, and we wish these to follow the order given by the MANTRA as it fits nicely to robot teleguide actions. We always Overview first, while Zooming, Filtering and Details are applied on demand [31] [35]. Automatic adaptation based on speed and distance to objects is an available option useful for specific environments and situations.…”
Section: Adaptive Viewsmentioning
confidence: 99%
“…Rather, we focused on evaluating the interface capability of delivering multiple inputs to operators (from GPS, IMU, Camera and 3D graphic model). We had an Internet connection with delays ranging from 1 to 4 secs, which is in line with several works in the literature [7] [31]. We exploited the data-associated timestamps in order to serve all inputs and response on first-in first-served schedule.…”
Section: A Sensor Data Misalignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heshmat et al [8] compared telepresence between a 2-D screen and an HMD, and found that people prefer the ability to look around with the HMD. Zhang et al [37] researched the use of redirected walking when using an HMD for teleoperation, and Stotko et al [30] built a model from the environment to be observed by the user while the robot moved. However, in [30], [37] the issue of VR sickness was avoided by using less scalable user interfaces, and in [8], [23] it was not considered at all.…”
Section: Previous Workmentioning
confidence: 99%
“…Adaptive and immersive interfaces have shown improvements in situational awareness, workload and performance of operators that manage multi-robot systems with both aerial, ground and manipulator robots [32]. Other recent work demonstrated the feasibility of reconstructing scenarios with RGB-D sensors and, at the same time, operating robots through VR head-mounted devices [33]. Others used Augmented Reality to teleoperate an industrial robot for assembly tasks, increasing the accuracy, efficiency and reducing the differences of skillfulness [34].…”
Section: State Of the Artmentioning
confidence: 99%